Kesiapan Implementasi E-Government Menuju Penguatan Sistem Inovasi Daerah (SIDa) Kota Kupang - Yohanes Payong (Badan Penelitian dan Pengembangan Daerah Kota Kupang, 2019)
One of the 2017-2022 Regional Government Innovation Programs is the implementation of E-Government in various Regional Apparatus organizations (OPD). For this reason, it is very necessary to map the current implementation of E-Government in The Government of Kupang City. This research evaluates nine dimensions, which are Information and Communication Technology (ICT) Connectivity, ICT Usage and Integration, Training, Human and Resource Capacity, Regional Policies and Regulations, Security, Access, Applications and Services. The results showed, many applications are offline. There are still 52.94% applications used offline, and 47.05% applications used online. Based on survey data, there are 15 Regional Apparatus Organizations (50%) stating that they do not fully utilize the online system. Meanwhile, related to the level of updating data and information on the website (26%) is not updated, and (30%) states frequently updated. Related to the ease of accessing data and information, 11 OPDs (36.6%) stated that it was difficult to access information. Thus, it can be concluded that the dimensions of training and human resource capacity have a value of 1.79 readiness and as much as 1.87 at the level of unprepared.